Intraspecific Resource Partitioning By Hampala Macrolepidota (Van Hasselt) In Lotic And Lentic Environment Of Kenyir Reservoir, Malaysia - Chowdhury , Ahmed jalal Khan (1995)

(untitled)
A study of Intraspecific Resource Partitioning on a tropical sport fish 'Side bar barb' Hampala macrolepidota van Hasselt, was carried out in lotic and lentic habitat at Kenyir Reservoir, Terengganu, Malaysia. Physico-chemical regimes of Kenyir Reservoir were also studied to determine the species ecological requirements. The water quality data showed that Kenyir Reservoir is suitable for fish culture. The most vital ecological factors, temperature and dissolved oxygen levels, were within the acceptable range for fish until 10.0 m depth. Waterlevel and rain fall both showed significant (P<.05) effects on the availability of fish in both habitats. A significant difference (P<. 05) of fish abundance have been observed in different depths of both habitat. Medium and large size fishes were ubiquitous in the study area. In the lotic habitat, medium and larger size fishes mostly used pool and riffle zones as their macrohabitat, whereas smaller size fishes preferred the rapid zone. In the lentic habitat, medium and large size fishes were found mostly around the submerged trees of the littoral area. Significantly, higher proportion (P<. 05) of larger fish were available in the lotic than in the lentic habitat throughout the season. In lotic habitat cobble, boulder and bedrock were predominantly used as substrate by small, medium and large size fishes respectively, whereas sand and clay were predominantly used by medium and large size in lentic habitat. Openwater area had remarkably less density of fish and availability of all sizes in both littoral and open water showed significant difference (P<.0 5).Habitat overlap values responsible for diet variation and food partitioning that evolved according to both temporal and ontogenic trends indicated that different size classes reduce spatial overlap by occupying different habitats and among depths within habitat. Segregation of sexes (aws < aw ) indicated that overlap within a habitat may be reduced by spatial separation of sexes. Niche breadth (Bi < 2) indicated that all size of Hampala macrolepidota appeared to be extreme specialist feeders. Occurrence of food partitioning was not found extensively between size classes of Hampala macrolepidota in Kenyir Reservoir. Diet overlap aw quantifying the sharing of food resources between the different size classes and high dietary overlap (aw >.6 0) between them indicates biological significance.